Hepatoprotective Activity Of Superliv Liquid In Ccl4 Induced Flks Syndrome In Commercial Broilers - Sonkusale, P. M.; Sawarkar, A. R.; Jumde, P. D. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A total of 75 day old broiler chicks were divided into three equal groups. Group A served as negative control. Group B (positive control) and C (treatment group) were intoxicated with CCl4 orally @ 1 ml/kg body weight after every 3rd day during 15-28 days of age. Treatment group C was given superliv liquid @ 10 ml/100 chicks / day in drinking water during 29th-42nd day of age. At the end of experiment, significantly (P<0.01) higher mean body weight and lower FCR was observed in treatment group C as compared to positive control group B. Similarly, significantly decreased levels of SGOT, SGPT, cholesterol, triglycerides, VLDL, creatinine and higher mean values of serum protein profile along with mild degenerative changes in liver and kidney of broiler from group C were observed as compared to group B indicating efficacy of superliv in ameliorating the toxic effects or FLKS induced by CCL4 in commercial broilers.